Upper Limbs Triaxial Accelerometry Signal Acquisition System for Parkinson’s Disease Tremor Study - Soto Domínguez, R.; Dorantes Mendez, G.; Mejía Rodríguez, A. R. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2020)
In this work, we proposed the design of a triaxial accelerometry signal acquisition system for the study and characterization of Parkinson’s disease tremor in upper limbs, using components and technologies commonly available in academic environments. The system consists of hardware and software stages, which were implemented by using commercial integrated circuits, the Arduino IDE and the Processing programming language. This allowed to decrease the cost compared to currently available options in the market and to properly personalize the functionality of the system (hardware and software) in order to fulfill the needs in terms of the acquisition of accelerometry signals to assess tremor in Parkinson’s disease. The system was tested in academic and research projects and the obtained data was compared qualitatively to the one obtained previously with a commercial system. The designed system is capable of measuring triaxial accelerometry signals from both upper limbs simultaneously, each sample contains data from six axes in the form of a comma separated string in order to be appended to a text file by the developed desktop application, and is sent to a personal computer via Bluetooth for further analysis.